1983
DOI: 10.1111/j.2042-3306.1983.tb01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on isoxsuprine hydrochloride for the treatment of navicular disease

Abstract: Summary A peripheral vasodilating agent, isoxsuprine hydrochloride, administered as an oral paste, was evaluated to determine its efficacy for the treatment of navicular disease. In a clinical trial, 13 horses with navicular disease were treated at a dose rate of 0.6 mg/kg body weight (bwt) twice daily for periods of six to 14 weeks. Twelve of the horses became completely sound while being treated, although two required a 50 per cent increase in dose. Nine of the horses have remained sound two to 10 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 12 publications
0
28
1
2
Order By: Relevance
“…Recently, it has been suggested that part of the therapeutic effects of isoxsuprine in horses could be mediated by producing analgesia (Brumbaugh et al., 1999), but our results do not support this hypothesis. This is the first report to assess the analgesic potential of isoxsuprine in horses and gives scientific support to the asseveration that isoxsuprine does not have any analgesic effect in horses (Erkert and MacAllister, 2002), and to the anecdotal report of lack of analgesia of isoxsuprine in horses (Rose et al., 1983).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, it has been suggested that part of the therapeutic effects of isoxsuprine in horses could be mediated by producing analgesia (Brumbaugh et al., 1999), but our results do not support this hypothesis. This is the first report to assess the analgesic potential of isoxsuprine in horses and gives scientific support to the asseveration that isoxsuprine does not have any analgesic effect in horses (Erkert and MacAllister, 2002), and to the anecdotal report of lack of analgesia of isoxsuprine in horses (Rose et al., 1983).…”
Section: Discussionmentioning
confidence: 54%
“…In vitro , isoxsuprine produces vasodilatation in blood vessel rings from healthy horses (Baxter et al., 1989; Belloli et al., 2000), an effect attributed to blockade of α 1 ‐adrenoceptors (Belloli et al., 2000). In vivo , increased thermographic temperature of the cannon bone, fetlock and coronary band of forelimbs of horses has been reported after oral isoxsuprine administration, which suggests that isoxsuprine increases blood flow in the distal forelimbs of horses (Rose et al., 1983; Deumer et al., 1991). However, oral and intravenous administration of isoxsuprine did not modify digital or laminar blood flow in healthy horses (Adair et al., 1997; Ingle‐Fehr and Baxter, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasodilation, vasoconstriction, arteriovenous shunts, and coagulation dysfunction have been incriminated as potential mechanisms for the disease 1–3 . Several drugs used routinely in equine practice for the treatment of vascular diseases of the foot, specifically laminitis, are believed to increase digital perfusion by changing vasomotor tone or cardiovascular function 1,4,5 . Isoxsuprine and pentoxifylline are thought to improve digital blood flow in horses 4,6 (JH Boucher, personal communication, 1993), and are used to treat ischemic conditions of the foot such as laminitis and navicular syndrome 4–7 …”
mentioning
confidence: 99%
“…Isoxsuprine also inhibits platelet aggregation 12 . In horses with navicular syndrome, improvement in lameness scores has been reported after oral and intravenous (IV) isoxsuprine treatment 4,6,7 . An increase in horse forelimb skin temperature measured by thermography was reported after isoxsuprine administration 4,10 .…”
mentioning
confidence: 99%